2007
DOI: 10.1038/sj.mt.6300240
|View full text |Cite
|
Sign up to set email alerts
|

2′-O-methyl-modified RNAs Act as TLR7 Antagonists

Abstract: RNA molecules such as single-stranded RNA (ssRNA) and small interfering RNA (siRNA) duplexes induce Toll-like receptor (TLR)-mediated immune stimulation after intracellular delivery. We have previously shown that selective incorporation of 2'-O-methyl (2'OMe) residues into siRNA abrogates cytokine production without reduction of gene silencing activity. Here we show that 2'OMe-modified RNA acts as a potent inhibitor of RNA-mediated cytokine induction in both human and murine systems. This activity does not req… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
182
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 277 publications
(191 citation statements)
references
References 37 publications
8
182
1
Order By: Relevance
“…It has been shown that 2′OMe backbone modifications in even 2 residues of an siRNA can abrogate these effects and, in this regard, we designed an siRNA with 2 modifications in the sense strand of the siRNA 27 . We complexed this siRNA with in vivo-jetPEI and injected the complexes into the tail veins of mice.…”
Section: Efficacy Of Systemic Administration Of Claudin-5 Sirnamentioning
confidence: 99%
“…It has been shown that 2′OMe backbone modifications in even 2 residues of an siRNA can abrogate these effects and, in this regard, we designed an siRNA with 2 modifications in the sense strand of the siRNA 27 . We complexed this siRNA with in vivo-jetPEI and injected the complexes into the tail veins of mice.…”
Section: Efficacy Of Systemic Administration Of Claudin-5 Sirnamentioning
confidence: 99%
“…[146][147][148] The recognition of ssRNA by TLR7 is both sequence-and motif-dependent, [149][150][151][152] and methylation of the 2' hydroxyl group in uridine leads not only to abrogation of TLR7 activation, 153,154 but also appears to antagonize the receptor. 155,156 These effects, understandably, have important consequences on the development of siRNA as viable therapeutic modalities, [157][158][159] and it is to be expected that future advances in controlling and modulating adventitious innate immune stimulation by siRNA will also add significantly to our understanding of the biology of TLR7 and, hopefully will lead to a rational evaluation of ssRNA as potential immune adjuvants.…”
Section: Intracellular Tlr7 Activation: Imidazoquinoline Ligandsmentioning
confidence: 99%
“…Consequently, it is possible to adjust the RNAi trigger structure and, in the case of synthetic RNAi triggers, apply chemical modifications to minimize acute immune stimulation risk, a prediction which can then be tested in predictive assays. 38 While capitalizing on this progress by licensing related IP has proven difficult, companies like Tekmira have created brand value by establishing themselves as early adopters and experts in this area. 8 Adverse side-effects stemming from the ability of siRNAs to function as microRNAs by dampening the expression of often hundreds of off-target genes is a safety concern especially in administering an RNAi therapeutic over extended periods of time (microRNA-type off-targeting).…”
mentioning
confidence: 99%